2020
DOI: 10.1186/s12879-020-4785-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 CRF01_AE subtype and HIV-1 DNA level among patients with chronic HIV-1 infection: a correlation study

Abstract: Background: The impact of HIV-1 subtype (CRF01_AE and non-CRF01_AE) on HIV-1 DNA levels in HIV-1 chronically infected patients with suppressive antiretroviral therapy (ART) remains poorly understood. To evaluate the correlation of HIV-1 subtype with DNA level, and identify baseline predictors of HIV-1 DNA decay. Methods: ART-naïve HIV-1-infected patients from two large multi-center studies in China were classified into CRF01_AE and non-CRF01_AE subtype groups. Peripheral blood samples were collected at baselin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…The higher infectivity observed in infection with this variant may be attributed to its enhanced replicative fitness over its pure subtype constituents and hence improved adaptation to its host. HIV-1 subtypes C, D, and the genetic variant CRF01_AE observed in our study have been associated with faster HIV-1 disease progression to AIDS [ 7 , 10 , 22 , 23 ] and advanced immunodeficiency. Evidence suggests that recombinant forms have a faster rate of disease progression when compared to pure lineages.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The higher infectivity observed in infection with this variant may be attributed to its enhanced replicative fitness over its pure subtype constituents and hence improved adaptation to its host. HIV-1 subtypes C, D, and the genetic variant CRF01_AE observed in our study have been associated with faster HIV-1 disease progression to AIDS [ 7 , 10 , 22 , 23 ] and advanced immunodeficiency. Evidence suggests that recombinant forms have a faster rate of disease progression when compared to pure lineages.…”
Section: Discussionmentioning
confidence: 53%
“…This makes it difficult to assess the effect of these less predominant viral clades. Studies carried out in China, where variant CRF01_AE is the most predominant clade, revealed that this variant is associated with fast progression to AIDS (with a shorter median time from the estimated date of seroconversion to AIDS) and advanced immunodeficiency (shorter median time from estimated date of seroconversion to CD4 cell count <100 cells/μl) as compared to non-CRF01_AE viral clades [ 22 , 23 ]. However, a study in Nigeria reported similar rates of CD4 cell count recovery across all subtypes [ 24 ], which is concordant with the results obtained in our evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we applied the PBMC samples to measure HIV reservoirs, considering the availability and convenience of acquiring samples. Despite the fact that HIV reservoirs would be mainly represented in lymphoid tissues and gut-associated lymphoid tissue (GALT) (71,72), our previous studies exhibited that the measurement of HIV reservoirs through peripheral blood also provided valuable information (73)(74)(75)(76). Finally, we did not further study the connection between IFN response and microbial translocation, which was reported as a significant cause of persistent immune activation among INRs (20,(77)(78)(79).…”
Section: Discussionmentioning
confidence: 91%
“…The high genetic diversity of HIV-1 represented by different subtypes may lead to the inaccuracy of HIV-1 DNA quantification [ 18 ]. In the large number of HIV infected samples we tested previously [ 19 , 20 ], the method was used to detect HIV-1 DNA in patients independent of subtypes. The quantification range for HIV-1 DNA using this assay was 20 to 5 × 10 6 copies/10 6 WBCs in our study.…”
Section: Discussionmentioning
confidence: 99%